2021
DOI: 10.2196/30747
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Self-Reported Web-Based Gambling Activity During the COVID-19 Pandemic: Cross-sectional Study

Abstract: Background The COVID‑19 pandemic has affected not only somatic health with over 3.7 million deaths worldwide, but also has had a huge impact on psychological health, creating what amounts to a mental health crisis. The negative effect of the pandemic on traditional addictions is well described and concerning, and the same has been seen for gambling. Objective This study explores self-reported web-based gambling behavior during the COVID‑19 pandemic in S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…It is important to identify how these individuals differ from the majority who reduce their gambling, to facilitate early identification and intervention for those whose mental health has been negatively affected during the pandemic. As noted by Claesdotter-Knutsson and Håkkanson ( 61 ), baseline problem gambling severity and psychological distress scores may be associated with an increase in gambling during the pandemic. However, a study by Gainsbury et al ( 62 ) found only moderate risk gamblers increased their gambling during the pandemic and these authors reported no association between psychological distress and increased gambling, highlighting the need for additional research on this topic.…”
Section: Future Directions and Conclusionmentioning
confidence: 81%
See 1 more Smart Citation
“…It is important to identify how these individuals differ from the majority who reduce their gambling, to facilitate early identification and intervention for those whose mental health has been negatively affected during the pandemic. As noted by Claesdotter-Knutsson and Håkkanson ( 61 ), baseline problem gambling severity and psychological distress scores may be associated with an increase in gambling during the pandemic. However, a study by Gainsbury et al ( 62 ) found only moderate risk gamblers increased their gambling during the pandemic and these authors reported no association between psychological distress and increased gambling, highlighting the need for additional research on this topic.…”
Section: Future Directions and Conclusionmentioning
confidence: 81%
“…One area for future research is the identification of factors that moderate the relationship between gambling availability and gambling behaviors. Though existing research indicates most people gambled less in response to the pandemic, a subset of individuals responded by increasing their gambling, and these individuals may experience more psychological distress and engage in more risky behaviors ( 34 , 59 61 ). It is important to identify how these individuals differ from the majority who reduce their gambling, to facilitate early identification and intervention for those whose mental health has been negatively affected during the pandemic.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…In the study carried out in March2021, primarily addressing potential COVID-19-related changes in the gambling market, ve percent of gamblers had ever self-excluded through the Swedish self-exclusion service [10]. In the study from 2020, seven percent of participants with 10 occasions or more of past-year online gambling had ever self-excluded [7].…”
Section: Discussionmentioning
confidence: 99%
“…The subjective, self-report-based information about self-exclusion may also be limited by recall bias. Nonetheless, the items addressing self-exclusion have been worded in the same way as in previous studies [7,8,10], making comparisons possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation